Metronomic chemotherapy in patients with metastatic breast cancer - Soriano-Lorenzo, Jorge (2020)
Metronomic chemotherapy is a type of chemotherapy whose toxicity is minimal. It consists of administering usual antineoplastic agents at intervals very close to each other and at relatively low doses for a prolonged time without periods of pharmacological rest. This therapy reduce toxicity and eliminates the need for supportive treatments, therefore, the use of this treatment modality in patients with metastatic disease is of great interest. Many investigations have evaluated the administration of antineoplastic drugs in metronomic schemes, both in monotherapy and in combination. The most studied drugs are cyclophosphamide, vinorelbine and capecitabine. Several studies have shown the efficacy and tolerance of this therapy combined with hormone therapy and immunotherapy. More scientific evidence is needed to define issues such as: patients who can obtain more benefit and the therapeutic combinations to be used according to the type of patients.